2000
DOI: 10.1590/s0004-27492000000300009
|View full text |Cite
|
Sign up to set email alerts
|

Estudo do comportamento da pressão intra-ocular em pacientes diabéticos, hipertensos e normais (Projeto Glaucoma)

Abstract: Purpose: To correlate the values of intraocular pressure (IOP) obtained by applanation tonometer (Haag-Streit, Bern, Switzerland) in patients with diabetes mellitus (with or without diabetic retinopathy), hypertension (with or without hypertensive diabetic retinopathy) and the normal population.Patients and Methods: Subjects participating in the Glaucoma Project (n = 924, 40 or more years old) were examined according to standard protocols including IOP measurement, fundoscopy, blood pressure and glucose determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
(8 reference statements)
0
0
0
9
Order By: Relevance
“…35 Jian et al in 2000, it was reported that IOP increased in patients with diabetic retinopathy and hypertension. 36 Pimentel et al in 2015, there was a significant relationship between diabetes and eye pressure. This study also found that postprandial IOP was higher than random IOP.…”
Section: Discussionmentioning
confidence: 93%
“…35 Jian et al in 2000, it was reported that IOP increased in patients with diabetic retinopathy and hypertension. 36 Pimentel et al in 2015, there was a significant relationship between diabetes and eye pressure. This study also found that postprandial IOP was higher than random IOP.…”
Section: Discussionmentioning
confidence: 93%
“…Exercícios utilizando treinamento de força em homens e mulheres com Po normal fisicamente ativos, apresentaram uma redução moderada da Po, sendo recomendada cautela na generalização dos resultados com relação à recomendação de exercícios de força para pacientes com Po elevada. Indivíduos com glaucoma deverão realizar exercícios de intensidades moderadas (8) . Na presente pesquisa, não houve diferença significante ao realizar os testes estabelecidos.…”
Section: Discussionunclassified
“…Segundo um estudo realizado com indivíduos com hipertensão arterial sistêmica e diabetes mellitus, observou-se que o valor médio da Po é progressivamente mais elevado quando se considera o tempo de instalação da doença hipertensiva sistêmica, cujo quadro e evolução são também fatores que contribuem para este aumento, principalmente quando associada a diabetes (8) .…”
Section: Effects Of Reading Exercise and Exercise Combined With Readunclassified
“…Já, segundo o trabalho desenvolvido pelo Baltimore Eye Survey, há uma associação de diabetes mellitus com o aumento da pressão intraocular; contudo esta elevação pouco expressiva, não encontra associação com a evolução do glaucoma de ângulo aberto(MAIA et al, 2000).Algumas pesquisas relataram uma associação entre DM e pressão aumentada no espaço intra ocular. Os altos níveis de glicemia podem levar a um gradiente osmótico e atrair fluido para o interior desse espaço culminado com a elevação pressórica (MENEZES; MORAES, 2020).Segundo a literatura atentou-se à medição da pressão intraocular, pois é sabido que o uso de Triancinolona no tratamento de edemas resistentes ao laser, tem como complicação o aumento desta.…”
unclassified